Application Of Role Play Method To Improve Students' Speaking Ability In Learning English - Primatur Riyanai; Bradhiansyah Tri Suryanto; Rizki Rinayah Rora (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This Classroom Action Research (CAR) aims to find real solutions in improving the speaking skills of 5B grade students of MI Nurul Mun'im. The main problem identified is low speaking skills with an average Pre-Cycle score of only 62.5 and a classical completion rate of 21.05%, which is caused by high speaking anxiety and limited fluency. The chosen methodological intervention is the Role Play Method in the context of functional buying and selling material ('How much is it?'). This study involved 19 students and was carried out in two cycles, with success indicators of KKM ≥ 75 and classical completion ≥ 80%. The results showed a significant increase. The average class score increased from 62.5 (Pre-Cycle) to 72.1 (Cycle I), and reached 81.0 in Cycle II. Classical completion increased to 89.47% in Cycle II. It was concluded that the application of effective and structured role-playing methods was able to overcome students' anxiety problems and improve their speaking skills at the basic level.